Nuda codzienności w sztuce Marzec Iriny Waśkowskiej - Charko-Klekot, Paulina (Studia Rossica Posnaniensia, 2023)
The article attempts to describe how everyday life and the ennui it entails influence the lives of the protagonists of Irina Vaskovskaya’s play March. The banality of everyday life is one of the main themes in this young author’s works – Vaskovskaya draws portraits of women that are bored and disillusioned with their shallow, bland life, who are waiting for a miracle to free them from the abyss of monotony. The protagonist of the play March stands out against the background of these characters. For her, the trivial everyday life becomes an incentive to abandon her current existence and look for happiness elsewhere (although the actions she takes are often destructive). In the case of the other characters, the lacklustre reality does not spark creativity, but only deepens their passivity and inertia. Vaskovskaya’s play is quite a sombre image of provincial Russia, whose inhabitants live in a state of numbness. While maintaining a semblance of normalcy, they flit between boredom and despair in relation to the meaninglessness of their existence.